2022
DOI: 10.1186/s12888-021-03677-2
|View full text |Cite
|
Sign up to set email alerts
|

Primary emotions as predictors for fear of COVID-19 in former inpatients with Major Depressive Disorder and healthy control participants

Abstract: Introduction There are reports of an increase in depressive symptoms and fear during the COVID-19 pandemic, in particular in patients with depression. This study investigates factors related to fear of COVID-19 in former inpatients suffering from depression and healthy controls by assessing variables typically associated with depression and anxiety disorders, i.e. stressful life events (SLEs), the primary emotions SADNESS, PLAY and SEEKING as well as dysfunctional emotion regulation strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 84 publications
(95 reference statements)
1
19
0
Order By: Relevance
“…The cited authors indicated associations of depression with SADNESS (β = 0.53), FEAR (β = 0.10), SEEKING (β = −0.10), and PLAY (β = −0.15). Comparable results were obtained in the pre-COVID-19 study conducted by Sanwald et al [86]. There were 44 patients treated for depression and 49 healthy controls in that project.…”
Section: Neural Emotional Systems and Early Maladaptive Schemas In De...supporting
confidence: 54%
See 2 more Smart Citations
“…The cited authors indicated associations of depression with SADNESS (β = 0.53), FEAR (β = 0.10), SEEKING (β = −0.10), and PLAY (β = −0.15). Comparable results were obtained in the pre-COVID-19 study conducted by Sanwald et al [86]. There were 44 patients treated for depression and 49 healthy controls in that project.…”
Section: Neural Emotional Systems and Early Maladaptive Schemas In De...supporting
confidence: 54%
“…As a result, the primary PLAY emotion was significantly negatively associated with fear of COVID-19. Interestingly, while there was a (non-significant) positive association between SADNESS and fear of COVID-19 in the healthy controls, SADNESS was negatively associated with fear of COVID-19 in the former inpatients [86]. Sanwald et al [87] also confirmed the increased activity of the SADNESS system with decreased activity of the SEEKING system among young women suffering from depressive disorders compared to male subjects.…”
Section: Neural Emotional Systems and Early Maladaptive Schemas In De...mentioning
confidence: 94%
See 1 more Smart Citation
“…Their findings indicated a strong correlation between the FoC and anxiety and moderate correlations between the FoC, depression, and stress. In another study, Sanwald et al ( 2022 ) focused on primary emotions (i.e., play, sadness, and seeking) as determinants for the fear of COVID-19 in former inpatients with healthy control and major depressive disorder. Their results indicated that depression severity and FoC were significantly lower in healthy controls than in former inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Because the data collection was done during the COVID-pandemic, we also applied the Fear of COVID scale (FCV-19S) with seven items in the German version as put forward in ( Sanwald et al, 2022 ) as a control variable; original version ( Ahorsu et al, 2020 ). The scale is answered on a five-point Likert scale ranging from 1 = strongly disagree to 5 = strongly agree.…”
Section: Methodsmentioning
confidence: 99%